FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN MASKER GEL PEEL- OFF DARI EKSTRAK BUAH STROBERI (FRAGARIA SP) DENGAN METODE DPPH - Utami, Anissa; Pomalingo, Dwina Ramadhani; Bastian, Irvan; Winarni, Gandes; Susanti, Debi; Yuristiawan, Yuristiawan; Alhabzy, Raihan Wisnu (PHRASE (Pharmaceutical Science) Journal, 2025)
Strawberries (Fragaria sp.) are plants rich in bioactive compounds such as anthocyanins, flavonoids, ellagic acid, and vitamin C, which act as natural antioxidants. This study aimed to formulate and evaluate peel-off gel mask preparations containing strawberry extract and to test their antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The research was conducted experimentally with three extract concentrations: F1 (2%), F2 (3%), and F3 (4%). The formulations were evaluated through organoleptic testing, homogeneity, pH, drying time, and spreadability. Antioxidant activity was analyzed based on IC50 values. The results showed that all formulations remained stable organoleptically during 4 weeks of storage, were homogeneous, had pH values of 4.72–5.37, drying times of 15–19 minutes, and spreadability between 5.1–6.1 cm. Antioxidant activity tests revealed that F1 had an IC50 value of 63.65 μg/mL, F2 of 57.75 μg/mL, and F3 showed the strongest activity with an IC50 value of 41.77 μg/mL, which is categorized as very strong. In conclusion, the F3 formulation (4%) demonstrated the best physical stability and the highest antioxidant activity.